2018
DOI: 10.1007/s00299-018-2260-2
|View full text |Cite
|
Sign up to set email alerts
|

QTL-Seq-based genetic analysis identifies a major genomic region governing dwarfness in rice (Oryza sativa L.)

Abstract: A major dwarfing region for plant height, asd1, was identified employing the next-generation sequencing-based QTL-Seq approach from a dwarf mutant and is demonstrated to be responsible for the dwarf nature with least penalty on yield in rice. The yield plateauing of modern rice is witnessed since many decades due to the narrow genetic base owing to the usage of a single recessive gene, i.e., semi-dwarf-1 (sd-1) for development of short-statured varieties throughout the world. This calls for the searching of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…MutMap analysis detected candidate genomic region, i.e., lm1 locus based on ∆ (SNP-index) that were further validated and fine mapped by SSR traditional map-based cloning, and were mapped between the SSR markers BARCSOYSSR_04_1429 and BARCSOYSSR_04_1435, which suggests the validity and robustness of MutMap-seq as a strategy for quick and efficient scanning of major genomic region for mutant phenotype on a genome-wide scale in soybean. The merits of BSA-seq method relative to other traditional mapping approaches for identifying the major genomic regions governing plant height, seed weight, seedling vigor and flowering time in soybean, chickpea and rice have been recently reported [26,59,60]. MutMap takes advantage of the high-throughput WGRS and BSA.…”
Section: Discussionmentioning
confidence: 99%
“…MutMap analysis detected candidate genomic region, i.e., lm1 locus based on ∆ (SNP-index) that were further validated and fine mapped by SSR traditional map-based cloning, and were mapped between the SSR markers BARCSOYSSR_04_1429 and BARCSOYSSR_04_1435, which suggests the validity and robustness of MutMap-seq as a strategy for quick and efficient scanning of major genomic region for mutant phenotype on a genome-wide scale in soybean. The merits of BSA-seq method relative to other traditional mapping approaches for identifying the major genomic regions governing plant height, seed weight, seedling vigor and flowering time in soybean, chickpea and rice have been recently reported [26,59,60]. MutMap takes advantage of the high-throughput WGRS and BSA.…”
Section: Discussionmentioning
confidence: 99%
“…This approach combined with Bulked segregant analysis, accompanied by whole genome re-sequencing technologies, is more effective and capable than the previous QTL detection methods (Takagi et al, 2013). Utilizing QTL-seq approach several QTLs and genes for different rice phenotypes (Takagi et al, 2013;Daware et al, 2016;Ogiso-Tanaka et al, 2017;Yang et al, 2017;Kadambari et al, 2018;Qin et al, 2018;Bommisetty et al, 2020;Nubankoh et al, 2020), soybean (Song et al, 2017;Zhang X. et al, 2018), chickpea (Singh et al, 2016;Deokar et al, 2019), tomato (Illa-Berenguer et al, 2015, groundnut (Kumar et al, 2020;Luo et al, 2019;Zhao et al, 2020), have been effectively identified. This approach has also been deployed across in several crops due to its inherent ability to understand both qualitative and quantitative traits (Table 2).…”
Section: Sequencing and Qtl-seq Based Trait Discoverymentioning
confidence: 99%
“…As mentioned in the introduction of this paper and Table 1 and Table 2, there are currently many available methods that combine the BSA of mixed DNA to make next-generation sequencing of responsible genes or QTL more efficient and rapid. Among these techniques, many QTL and genes using QTL-seq technique for different rice phenotypes [25,27,29,58,59,60], cucumber [35], tomato [36], chickpea [37], and soybean [33,34] have been effectively isolated.…”
Section: Qtl Seqmentioning
confidence: 99%